Cover Image: Volume 83 Issue 3. Issue 3 (8th January 2023) - Graham, Mindy K.; Chikarmane, Roshan; Wang, Rulin; Vaghasia, Ajay; Gupta, Anuj; Zheng, Qizhi; Wodu, Bulouere; Pan, Xin; Castagna, Nicole; Liu, Jianyong; Meyers, Jennifer; Skaist, Alyza; et al.
Abstract : The cover image is based on the Original Article Single‐cell atlas of epithelial and stromal cell heterogeneity by lobe and strain in the mouse prostate by Mindy K. Graham PhD et al., https://doi.org/10.1002/pros.24460